Evaluasi Usability Aplikasi English Competency Test (ECT) Menggunakan Metode Computer System Usability Questionner (CSUQ): Studi Kasus Pusat Bahasa Institut Teknologi Telkom Purwokerto - Atika Rahmadani Utami Br Ginting; Sarah Astiti; Khairun Nisa Meiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The advancement of the digital era provides many conveniences in various fields. This is because its presence can support the sharing of human activities. One of the conveniences that can be felt is the digital transformation in the implementation of English certification to improve the effectiveness and quality of its implementation. English certification through a web-based English Competency Test (ECT) is a form of digital transformation used to certify English at the Telkom Institute of Technology Purwokerto. However, in practice, the use of the English Competency Test (ECT) system still has several shortcomings, such as the appearance on the English Competency Test (ECT) is less attractive and difficult to understand, the access process is less responsive and some features are not functioning properly. Therefore, to correct the existing deficiencies, it is necessary to evaluate the effectiveness of use. This study is here to analyze the quality assessment of the English Competency Test (ECT) system. By using the Computer System Usability Questioner (CSUQ) instrument in the form of a questionnaire to assess the effectiveness, efficiency and convenience provided by ECT. The results showed that the usability of the English Competency Test (ECT) system was “Neutral” with a feasibility percentage of 58%. Neutral indicates that the English Competency Test (ECT) can be used, but still cannot be said to be good. Based on the research results, improvements can be made to the Information Quality section by providing error messages and improvements and improvements to the Interface Quality section to make it more user friendly.